Up-front dissection of the uterovesical space or “bladder-first approach” reduces hemorrhage and bladder injury during hysterectomy for placenta accreta spectrum: reconfirmed in 78 more cases in a prospective single-center studyAJOG Global Reports at a Glance - Pradip Kumar Saha, MD, MAMS; Rashmi Bagga, MD, DNB; Rimpi Singla, MD; Aashima Arora, MD; Vanita Jain, MD; Vanita Suri, MD; Kajal Jain, MD; Parveen Kumar, MD, DM; Nalini Gupta, MD; Ashish Jain, MD; Tulika Singh, MD; Ravimohan S. Mavuduru, MS, MCh (AJOG Global Reports)
BACKGROUND: Cesarean hysterectomy for placenta accreta spectrum disorder may be associated with severe hemorrhage because of placental invasion of the myometrium and the uterovesical space or parametrium. It leads to serious complications, such as massive hemorrhage requiring massive transfusion, coagulopathy, bladder and ureteric injuries, need for intensive care unit admission and prolonged hospital stay. To reduce the complications of cesarean hysterectomy for placenta accreta spectrum disorder, ongoing efforts are being made to develop different surgical approaches. In previous 12 cases upfront dissection of uterovesical space (bladder-first approach) before delivery of the neonate was observed to reduce hemorrhage arising from extensive neovascularization in this area and bladder injury. OBJECTIVE: This study aimed to assess the efficacy of the bladder-first approach in a large sample to reduce the complications of cesarean hysterectomy for placenta accreta spectrum disorder. STUDY DESIGN: This study presented data of 78 women (2017–2022) who underwent cesarean hysterectomy for placenta accreta spectrum disorder using the “bladder-first approach” from a tertiary care institute in Chandigarh, India. In this surgical approach, dissection of the uterovesical fold from the lower uterine segment to the cervix was performed before making the uterine incision for delivery. During this dissection, vascular areas were isolated and coagulated with bipolar electrosurgery or ligated with silk suture and then divided. RESULTS: The 78 women with placenta accreta spectrum disorder underwent cesarean hysterectomy under general anesthesia. The mean gestational age was 35.0±2.5 weeks (range, 25.4–38.0), the mean blood loss was 1.56±1.06 L (range, 0.40–5.00 L), and the mean number of blood transfusions was 2.08±2.10 units (range, 0.00–9.00). Bladder injury occurred in 3 of 78 women (3.8%), and intensive care unit admission (for ≤24 hours) was needed by 3 of 78 women (3.8%). Histology was available in 73 of 78 women (19 with placenta percreta, 23 with placenta increta, and 31 with placenta accreta). There were 3 of 78 antenatal stillbirths. Of note, 75 women had live-born neonates, including 2 pairs of twins. The Apgar score of ≤7 at 5 minutes was seen in 6 of 77 neonates, and 20 of 77 neonates required neonatal intensive care unit care. There was 1 neonatal death on day 3 of life because of extreme prematurity and sepsis. In addition, 74 women went home with neonates, including 2 pairs of twins. CONCLUSION: Our data support that up-front dissection of the uterovesical space or “bladder-first approach” reduces hemorrhage and bladder injury during cesarean hysterectomy in placenta accreta spectrum disorder, with no adverse effect on neonatal outcome. Achieving peripheral vascular control of the neovascularized uterovesical area before achieving control of the central vascular supply (uterine arteries) reduced intraoperative hemorrhage. This approach requires no additional resource and can be implemented easily in developing countries.